SYSTEM OF SUPERVISION OF THE FINANCIAL MARKET IN THE REPUBLIC OF LITHUANIA - Sudavichus , Бронюс Броневич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2023)
The article deals with the analysis of the existing model of the organization of supervision of financial market in the Republic of Lithuania – from the period of it’s foundation to the establishment of the consolidated supervision of financial market.